Comparative transcription of right- and left-handed poly[d(G-C)] by wheat germ RNA polymerase II. - Durand, R (1983)
The template properties of left-handed synthetic polymers, the Z* form of poly[d(G-C)] and the Z form of poly[d(G-m5C)], have been investigated using an eucaryotic RNA polymerase, the class II enzyme from wheat germ. Results from a comparative kinetic study of transcription using the polynucleotide substrates in the B and Z conformations are reported. Optimal conditions for enzyme activity compatible with the preservation of the desired template conformation were determined. On the basis of several criteria, both physical (c.d. spectra of the polymers, sedimentability of the Z* form) and biochemical, it was demonstrated that the left-handed conformations of poly[d(G-C)] and poly[d(G-m5C)] serve as templates for wheat germ RNA polymerase II. The level of incorporation was less than that exhibited by the B form of poly[d(G-C)], the relative activity being a function of the precise experimental conditions. Activity ratios (Z*/B or Z/B) ranged from 0.1 to 0.5. The effect of various incubation parameters, including pH, salt concentration, temperature, and the presence of dinucleoside monophosphate primers were investigated. The Km values for nucleoside triphosphate substrates were slightly smaller for the Z* form of poly[d(G-C)] than for the B conformation. Titration of DNA (Z* or B) with enzyme and reciprocal experiments suggested that the reduced activity of left-handed templates might derive from the availability of fewer and/or lower affinity sites for initiation and/or translocation on these templates. Specific antibodies raised against left-handed DNA strongly inhibited the observed transcription of Z* and Z DNAs by wheat germ RNA polymerase II.